Adsorption of triclosan from aqueous solution onto char derived from palm kernel shell - Triwiswara, Mutiara; Lee, Chang Gu; Moon, Joon Kwan; Park, Seong Jik (Desalination and Water Treatment, 2020)
Char derived from palm kernel shell (PKS-char) was evaluated as an adsorbent for the removal of triclosan, an antimicrobial agent used in consumer products, from aqueous medium. Despite the low specific surface area of PKS-char, its average pore size is 4.1 nm, which is suitable for the penetration of triclosan into the inner pores. Kinetic experiments showed that with initial triclosan concentrations of 5 and 50 mg L−1, adsorption equilibrium was reached at 6 and 12 h, respectively. The Langmuir model described the equilibrium adsorption of triclosan to PKS-char more suitably than the Freundlich model, indicating that triclosan was adsorbed on PKS-char as a monolayer. The maximum capacity of PKS-char for triclosan adsorption was 88.854 mg g−1, which is higher than that of some commercial activated carbon samples. Triclosan adsorption decreased gradually as the pH increased from 4 to 8, but decreased sharply above pH 8. Thermodynamic experiments showed that the adsorption of triclosan by PKS-char is endothermic and spontaneous under the present experimental conditions. It can be concluded that PKS-char is a low-cost but effective adsorbent for the removal of triclosan from aqueous solutions.
Keywords: Adsorption; Char; Low-cost adsorbent; Palm kernel shell; Triclosan